Kesultanan Serdang dan Jejak Peninggalannya - Fivi Herviyunita; Irwansyah Irwansyah; Rina Devianty (Medan Resource Center, 2021)
This article aims to discuss the history of the Serdang Sultanate Palace. The Serdang Sultanate is one of the Malay Sultanates of East Sumatra, a fraction of the Deli Sultanate, which is centered in the Province of North Sumatra. The establishment of the Serdang Sultanate Palace began when Tuanku Umar Johan Pahlawan Alam Shah Vocational Junjungan built the Tanjung Puteri Palace. Tuanku Umar was the first Sultan of Serdang to build the Tanjung Puteri Palace in 1750. The Serdang Sultanate Palace is a relic of the Sultanate that was previously built to be a resting place or throne for the Serdang Sultanate at that time, in addition to being a resting place, the Serdang Sultanate Palace was also a place to perform various activities. Activities and government systems in carrying out any activities that are closely related to the Sultanate. This research uses the historical method with an archaeological approach. The historical method is used to describe events that occurred in the past. The archaeological approach is used to find information about the relics of the Serdang Sultanate Palace as historical relics. According to Grahme Clark, who wrote his theory in Archeology and Society, archeology is a systematic study of ancient objects as a tool to reconstruct the past.